Postharvest quality of peaches harvested from integrated and conventional production systems - Seibert, Eduardo; Casali, Michel Elias; Leão, Marcos Laux de; Pezzi, Ernani; Corrent, Adriana Regina; Bender, Renar João (Pesquisa Agropecuaria Brasileira, 2007)
Over three years the postharvest quality of 'Marli' peaches harvested from the integrated (IFP) and conventional production (CFP) systems was evaluated. The peaches were harvested from commercial orchards of Prunus persica at two locations close to the city of São Jerônimo, RS, Brazil, and stored at 0.5°C for 10, 20 or 30 days. The peaches were evaluated at harvest, at retrieval from storage and after ripening periods at 20°C. No differences in fruit weight losses were determined. Decay incidence was low, and no differences were detected amongst systems in both 2001 and 2002 seasons, but in the 2000 season CFP peaches were more decayed. Flesh firmness of peaches from the IFP system were greater than CFP fruits in the years 2000 and 2001. In 2002, firmness changed little during storage and ripening. Peaches from the IFP in 2000 had higher titratable acidity and lower soluble solids. In the 2000 season, flesh browning was observed in decayed fruits, always at ripening after 20 or 30 days of cold storage Chilling injuries such as browning, woolliness and leatheriness ocurred in 2002. There were no differences amongst systems related to peach quality.